The Role of Canon in the Study of Hinduism and Some Notes About Bourdieu: A Response to Stephen L. Young - Llewellyn, John Earl (Method & theory in the study of religion, 2020)
This response to Stephen Young’s article begins with his use of the term doxa, drawn from Pierre Bourdieu. For Bourdieu doxa are the unspoken assumptions that undergird social hierarchy, assumptions that are only exposed during times of historical change. It is unclear if Young intends that the exposure of what he calls New Testament studies’ “protectionism” is a sign that the field has undergone such a change. The second part of the response is about the applicability of this kind of analysis to the study of Hinduism in North America, concluding that protectionism concerning the interpretation of the scriptural canon does not seem to be operative there. However, there is a more or less similar controversy about the study of Hinduism by outsiders.